Managerial Judging and Substantive Law - Tobias Barrington Wolff (Washington University Law Review, 2013)
In this Article, I examine the interface between substantive law and managerial judging. My aim is not to criticize the dominant strain of current scholarship, with its focus on endogenous values in the practice of judging. That work has posed important questions that have properly captured the attention of Academy, Bar and Bench. It is rather to ground that ongoing discussion in a richer account of the role that substantive legal policy can and should play in defining the role of the judge, constraining judicial options in some cases, and legitimizing judicial initiative in others.
Keywords: managerial judging; September 11; Federal Rules of Civil Procedure; substantive; Abe Chayes